Effectiveness of Acupressure on The Pericardium Point P6 And Zusanli St36 Against Nausea, Vomiting In 1st Trimester Pregnant Women - Zahra, Raisatul; Nurhasanah, Cut; Fitriani, Fitriani (Journal of Midwifery and Nursing, 2024)
Nausea,vomiting, common symptoms of the first trimester of pregnancy, occur approximately after 6-10 weeks, in 60%-80% of primigravidas and 40-60% of multigravidas. WHO estimates that 14% of all pregnant women experience nausea and vomiting. In Indonesia, of the 2,203 pregnancies that were completely observed, 534 mothers experienced nausea and vomiting. Data from Ingin Jaya Community Health Center, there were 933 pregnant people in 2021, Visit 1 (K1) coverage was 715 people. In 2022, 60 pregnant women will visit community health centers, 45 people will experience nausea and vomiting in the first trimester. Research design ; Quasi-experimental observation of two groups, pre-test and post-test. Two groups of research subjects; P6 pericardium acupressure and Zusanli ST36 acupressure each group amounted to 16 respondents. The research was carried out in the work area of the Ingin Jaya Aceh Besar Community Health Center in April -May 2023. Data analysis; Paired T test to see the results of the pre and post test of P6 and ST36 acupressure and the Independent T test to compare the frequency of nausea in the 2 groups. Research result; P6 and ST36 acupressure effectively reduced the frequency of nausea and vomiting before and after treatment, the p value for each group was (0.001<0.05), the average rank for P6 acupressure was 17.81 and the average rank for ST36 was 15.19. P6 pericardial acupressure is more effective than ST36 acupressure. Complementary methods are recommended for dealing with first trimester nausea and vomiting considering that medical management poses a risk to organogenesis